2016
DOI: 10.1055/s-0036-1572531
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Sex Differences in Intrapartum Electronic Fetal Monitoring

Abstract: Objective The article aimed to estimate differences in electronic fetal monitoring (EFM) patterns in term gestations attributable to fetal sex. Study Design We conducted a prospective cohort study of consecutive, singleton, nonanomalous, term gestations that labored during admission. EFM characteristics in the 30 minutes prior to delivery were evaluated. Logistic regression models estimated adjusted risks for EFM features by sex. To further estimate the impact of sex, we limited the analysis to gestations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Male fetuses were also found to be at increased risk for both repetitive variable decelerations (aOR: 1.24, 95% CI: 1.05–1.47) and prolonged decelerations (aOR: 1.21, 95% CI: 1.03–1.42). This study suggests that there may be significant sex differences in EFM patterns at term among pregnancies without evidence of academia (37). One explanation of these differences is that brain anatomy and the chemistry of neuronal transmission is affected by the protocadherin gene expression in the brain.…”
Section: Methodsmentioning
confidence: 77%
“…Male fetuses were also found to be at increased risk for both repetitive variable decelerations (aOR: 1.24, 95% CI: 1.05–1.47) and prolonged decelerations (aOR: 1.21, 95% CI: 1.03–1.42). This study suggests that there may be significant sex differences in EFM patterns at term among pregnancies without evidence of academia (37). One explanation of these differences is that brain anatomy and the chemistry of neuronal transmission is affected by the protocadherin gene expression in the brain.…”
Section: Methodsmentioning
confidence: 77%
“…While some studies found no significant differences between male and female FHR during the first and second trimester (Neiger et al, 2004; McKenna et al, 2005), different intrapartum FHR patterns have been reported for two genders (Porter et al, 2016). Another study on term fetuses just before the labor, reported significantly lower values of most linear HRV measures for female fetuses compared to male fetuses, in both IUGR and control groups, as well as higher entropy indices in the control group (Gonçalves et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Male fetal sex is an independent risk factor for preterm birth (PTB) (Brettell et al, 2008; Challis et al, 2013; Ingemarsson, 2003; Zeitlin et al, 2004), gestational diabetes (GDM), and macrosomia and cord complications (cord prolapse, nuchal cord, true umbilical cord knots) (Sheiner et al, 2004; Verburg et al, 2016). Males also have a higher risk of complications during labor and delivery, such as failure to progress during the first and second stages of labor (Sheiner et al, 2004), nonreassuring fetal heart patterns (Dawes et al, 1999; Porter et al, 2016), cesarean section (CS) delivery (Eogan, 2003; Lurie et al, 2004), and neonatal morbidity and mortality (Mondal et al, 2014; Stevenson, 2000).…”
mentioning
confidence: 99%